Revolutionizing pediatric neurology care: telemedicine advancements and regulatory impact in the Northeast of Brazil - Rodrigues, Daniela Laranja Gomes; Frota, Melina Alves da; Malta, Maísa Vieira da Silva; Maeyama, Marcos Aurélio; Padilha, Frederica; Miyauchi, Adriana; Senra, Vanessa dos Santos Gonçalves; Silva, André Felipe Martins de Araújo; Santos, Deyse Mirelle Souza; Castro Filho, Eno Dias de; Sousa, Nídia Cristina de; Pinho, Ana Paula Marques de; Hahne, Fernanda Saks (Arquivos de Neuro-Psiquiatria, 2025)
Background Telemedicine, a patient-centered approach that leverages technology, has emerged as a cost-effective solution to provide comprehensive medical services for acute and chronic conditions.Objective We aim to document the experiences of pediatric neurologists using teleconsultations within the TeleNortheast program, a specialized medical assistance initiative in the Northeast of Brazil.Methods A retrospective analysis of teleconsultations was conducted from January to October 2023. Data from 546 teleconsultations, involving 506 pediatric patients, were extracted from medical records. Consultations were conducted between pediatric neurologists in São Paulo and primary care professionals in Sergipe. The analysis included patients' demographics, diagnoses, and outcomes.Results Of the 506 teleconsultation patients seen, 89% continued treatment within their primary care settings without needing in-person referrals. Discharge was observed in 9.5% of cases, and only 1.4% required specialized in-person care. The most frequent diagnosis was autism spectrum disorder (19.1%), followed by epilepsy (7.1%), attention-deficit/hyperactivity disorder (6.7%), and intellectual disability (5.9%). A cost-saving analysis indicated that teleconsultations avoided significant transportation costs, which could reach up to R$ 21 thousand for travel and feeding expenses.Conclusion The results highlight the effectiveness of teleconsultations in improving access to pediatric neurological care in underserved regions, reducing the need for in-person counseling, with the potential to provide significant cost savings for the public health system. The TeleNortheast program demonstrates the potential of this approach to bridge healthcare gaps, particularly in regions with limited access to specialized care.
Keywords: Telemedicine; Public Health Systems; Neurology; Child